Housing and urban planning in a globalising economy - Karuppannan, Sadasivam (2008)
The idea that housing is quite central to leading a good life is not a new one. It is perhaps the most dominant objective of city master plans throughout the developing world. There are different approaches to housing depending on the planning regime followed. For example, Delhi has a long tradition of master plans since 1960s, a comprehensive approach to landuse planning which other cities in India aspire to achieve. The growth rate of the Indian economy remained stuck at its low traditional point of 3 per cent a year for a very long time. When India liberalised its economic policies in the mid 1990s, the growth rate picked up as expected. India is now getting used to its much higher rate of growth, first around 6 per cent a year and now about 9 per cent, occasionally touching 9.5 per cent. Much of the growth is said to have benefitted the urban population. It is relevant to investigate how the recent economic growth has facilitated the development of housing in Delhi, one of the largest cities in India with comprehensive land use planning in force. Delhi like other Indian cities have had its share of migration from country side and informal housing to a tune of about 40% until the 1990 which incidentally mark the beginning of economic liberalisation. A new master plan (Delhi 2021) has recently come into force wherein housing is again on the top of the agenda. This paper scrutinise the role of planning in promoting housing for all income groups including slums and informal settlements. It will also draw lessons of the impact of renewed economic growth and how best landuse planning can help achieve better quality of housing in cities in growing economies of developing countries.